Bahasa Inggris: Bahasa Inggris - Muhamad Safi'i; Akhmad Irfan; Rouf Muhammad; Suheri Suheri; Yafid Effendi (Universitas Wahid Hasyim, 2026)
Cavitation is a major issue in centrifugal pumps because it impacts their performance and efficiency. Experimental research was conducted to investigate the effect of the number of impeller blades and mass flow rate on the cavitation phenomenon in centrifugal pumps, as well as to characterize them. The Ebara brand centrifugal pump type 65x50 FSS4JA used in the TCU installation of the Casting Machine has a number of blades of 4 and 6 with a fixed inclination angle of 60° as the object of research. The fluid mass flow rate varies with values ​​of 1.67 kg/s, 3.33 kg/s, 5.67 kg/s, and 7.33 kg/s. The research findings show that the highest cavitation occurs in the centrifugal pump with 4 blades, with an NPSH value reaching 2.02 at a mass flow rate of 5.67 kg/s, while the lowest value is found in the pump with 6 blades with an NPSH of 1.88 at a mass flow rate of 7.33 kg/s. A 6-blade centrifugal pump operating at a mass flow rate of 7.33 kg/s demonstrated the best results in this study and is feasible for field application. Keywords: Impeller, Cavitation, Pump, Centrifugal.